True navigation in migrating gulls requires intact olfactory nerves - Wikelski, Martin (Sci Rep, 2015)
During migratory journeys, birds may become displaced from their normal migratory route. Experimental evidence has shown that adult birds can correct for such displacements and return to their goal. However, the nature of the cues used by migratory birds to perform long distance navigation is still debated. In this experiment we subjected adult lesser black-backed gulls migrating from their Finnish/Russian breeding grounds (from >60°N) to Africa (to < 5°N) to sensory manipulation, to determine the sensory systems required for navigation. We translocated birds westward (1080 km) or eastward (885 km) to simulate natural navigational challenges. When translocated westwards and outside their migratory corridor birds with olfactory nerve section kept a clear directional preference (southerly) but were unable to compensate for the displacement, while intact birds and gulls with the ophthalmic branch of the trigeminal nerve sectioned oriented towards their population-specific migratory corridor. Thus, air-borne olfactory information seems to be important for migrating gulls to navigate successfully in some circumstances.